Hinduism in a Muslim state: The case of Malaysia - Ramanathan, K. (Asian journal of political science, 1996)
According to the author, Islamic resurgence in Malaysia represents a confluence to several different streams of styles of faith and behaviour. Against the background of Islamic revivalism in this country, the author attempts to show how this revivalism has served to rekindle or reactivate the Hindus in Malaysia into taking a serious look at their own religion. He notes that, in many ways, this re-evaluation has caused changes within the Hindu community. (DÜI-Sen)